2018
DOI: 10.3390/app8101741
|View full text |Cite
|
Sign up to set email alerts
|

Study on Microstructure and Fatigue Damage Mechanism of 6082 Aluminum Alloy T-Type Metal Inert Gas (MIG) Welded Joint

Abstract: In this experiment, the T-joint of a 6082 aluminum alloy was welded by metal inert gas (MIG) welding and a fatigue test was carried out at room temperature. The mechanisms of generating pores and of fatigue fracture in welded joints are revealed in the case of incomplete penetration. There are two main types of pores: pores that are not welded and pores that are near the upper weld line of the weld. During welding, bubbles in the molten pool are adsorbed on the surface oxide film that is not penetrated, and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…It was found that preheating the weldment at 100 • C to 200 • C could significantly reduce the loading force and suppress the creation of fractures. In another work focusing on the microstructure and fatigue damage of metal insert gas welding Al6082, incomplete penetration was identified as the dominant factor for limited welding strength [10]. For low-temperature soldering studies, Yan et al [11] studied the aging effect of Pb-rich phase on Sn-Pb alloys, and Xue et al [12] studied the effect of γ-irradiation on the formation of micro-voids.…”
Section: Innovative Processing On Micro/nanojoiningmentioning
confidence: 99%
“…It was found that preheating the weldment at 100 • C to 200 • C could significantly reduce the loading force and suppress the creation of fractures. In another work focusing on the microstructure and fatigue damage of metal insert gas welding Al6082, incomplete penetration was identified as the dominant factor for limited welding strength [10]. For low-temperature soldering studies, Yan et al [11] studied the aging effect of Pb-rich phase on Sn-Pb alloys, and Xue et al [12] studied the effect of γ-irradiation on the formation of micro-voids.…”
Section: Innovative Processing On Micro/nanojoiningmentioning
confidence: 99%
“…Various codes and standards as well as recommended practices (e.g., [6,7]) are widely adopted for fatigue evaluation of welded joints. The fatigue life of a welded joint is significantly influenced by the stress concentration effect at welded joints [8][9][10][11]. The study of characterizing the stress concentration effects and achieving effective notch stress calculation at welds are important research directions in the field of predicting the fatigue life of welded components.…”
Section: Introductionmentioning
confidence: 99%
“…50 steel material, a probabilistic S-N curve does not exist. The main goal of the S-N curves analysis is related to the strength material behavior and its correlation with the defined stress ratio [1][2][3][4]. Structural elements are subjected to a range of stress values, so to determine the probabilistic S-N curve, any material steel is necessary [1][2][3]5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of the S-N curves analysis is related to the strength material behavior and its correlation with the defined stress ratio [1][2][3][4]. Structural elements are subjected to a range of stress values, so to determine the probabilistic S-N curve, any material steel is necessary [1][2][3]5,6]. Despite this, currently, in structural design, two different approaches have been used, and they are: (1) the application of a failure theory to determine if the designed element is safe or not; and (2) the fatigue approach [1,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation